Pola Perilaku Masyarakat terhadap Penggunaan Program Surabaya Single Window (SSW) sebagai Perizinan Online dalam Upaya Menekan Tindakan Korupsi, Kolusi, dan Nepotisme di Surabaya - Agus Widiyarta; Catur Suratnoaji; Sumardjijati (Faculty of Law Hang Tuah University, 2016)
Surabaya Single Window (SSW) is one of innovative program from the Government of Surabaya City as public service to issue license by online in actualizing the clean governance. The research results of the Investment Coordinator Body (Badan Koordinasi Penanaman Modal/ BKPM) Surabaya showed that 65% of Surabaya people still use manual license system and 35% of them use online system. Therefore, it is necessary to identify factors that motivate and hinder the behavior of Surabaya people to use SSW program as online license system. This research use descriptive method by sampling 300 respondents who are spread with cluster system by dividing respondents proportionally in 4 areas of Surabaya. The data are gained through questionnaire to people of Surabaya who have processed license in Surabaya city. The result of the study shows that the level of Surabaya people understanding towards SSW program as online license system is good enough. However, their behavior shows that majority of the the people using SSW is still little. The hindrance factors were: 1) the procedure of SSW program is rated as complicated and complex; 2) license process is not free procedure, it need some fee to make the process faster; 3) Surabaya people has high context culture which make them feel that they need to meet to every need.